MAKNA HIDUP DI LERENG GUNUNG RAUNG BAGI MASYARAKAT DESA PRENGPADDUH - Absor, Much. Ulil; Handayani, Baiq Lily (Jurnal ENTITAS SOSIOLOGI, 2016)
Abstract The research observed the life of people who live on the slopes of Mount Raung, precisely in Prengpadduh Village. They live on the slopes of Mount Raung with a radius distance of 7 km from Mount Raung and including KRB II with the threats of hot clouds, lava eruptions, lava rain, heavy ash rain, avalanches of volcanic debris, or hurl of incandescent rocks, but they still survive to stay at the area. Using the theoretical framework of social action of Max Weber and Verstehen method, the researcher observed how the meaning of life on the slope of Mount Raung for Prengpadduh Village is. In this research, the researcher used the technique of interview, observation, and literature review. The used determination technique of informants was purposive, and triangulation technique was used as a test of the data validity. The research result showed that Prengpadduh Village had the meaning of life on the slopes of Mount Raung as the source of life, as a comfortable place to live and as a place of social relationships. On the other sides, people interpreted the disaster as an event that disrupt the continuity of daily life, such as the declining quality of the latex, the contamination of an open water tank, the damaged coffee plants, the grass for fodder affected by volcanic ash, the disrupting of driving, the strong winds that knock down the pine trees and houses, the disrupting of rain to work activities, and the damaging of electronic devices caused by lightning. Keywords: Disaster, The Meaning of Life, and The Slope of Mount Raung